Response to Some Varieties of Onion (Allium ascalonicum L.) in Manure Application with Different Doses - Sri Mursiani Arifah; Mohammad Yazidhul Khasan; Machmudi Machmudi; Aulia Zakia; Padhina Pangestika; Fatimah Nursandi (Agrosains : Jurnal Penelitian Agronomi, 2025)
Shallot farmers in Poncokusumo District have struggled with crop failures due to unsuitable soil types. Addressing this, a study was conducted to evaluate the optimal manure dosage and the best shallot varieties for improving production. The research, held from October 2023 to January 2024 in Wonorejo Village, applied a Randomized Complete Block Design (RCBD) with factorial arrangements, including two factors: shallot varieties (Batu Ijo, Tajuk, Super Philip) and manure dosages (15 t/ha, 25 t/ha, 35 t/ha), each replicated three times. Data were analyzed using ANOVA and a 5% BNJ test. Growth observations began at 14 days after planting and continued every 10 days, measuring plant height, leaf count, and tillers. Yield parameters included wet and dry weights per clump, number of bulbs, bulb diameter, and total harvest yield. Results showed significant interactions between manure dosage and variety, with V1D1 (Batu Ijo + 15 t/ha goat manure) achieving higher yields. Additionally, Batu Ijo consistently outperformed other varieties across all variables, demonstrating greater plant height, bulb diameter, and overall yield. This suggests Batu Ijo with moderate manure dosage as an optimal combination for enhanced shallot production.